Resolving Challenges of Mass Transport in Non Pt-Group Metal Catalysts for Oxygen Reduction in Proton Exchange Membrane Fuel Cells. Issue 9 (26th May 2018) - Pavlicek, Ryan; Barton, Scott Calabrese; Leonard, Nathaniel; Romero, Henry; McKinney, Sam; McCool, Geoffrey; Serov, Alexey; Abbott, Daniel; Atanassov, Plamen; Mukerjee, Sanjeev
Abstract : Mass transport properties of a pair of non-Platinum Group Metal (non-PGM) catalysts in proton exchange membrane fuel cells (PEMFCs) were evaluated through methods developed by Reshetenko et al., demonstrating that the use of different carrier gases can allow for the determination of the mass transport coefficient for oxygen in the gas phase and the electrolyte phase. The gas-phase and non-gas-phase resistances can be elucidated from the slope and intercept, respectively, of the total mass transport coefficient plotted as a function of molecular weight. It was determined through these experiments that the primary sources of mass transfer limitations of the non-PGMs when compared to the PGMs were the catalyst layer (non-gas-phase), rather than the flow fields (gas-phase, primarily Knudsen Diffusion effects), and the gas diffusion layer. This work was combined with a pseudo-2D, isothermal, steady state numerical model to estimate the gas-phase mass transfer coefficient and the fraction of hydrophobic, gas-phase pores in the catalyst layer. Sensitivity studies were also carried out, allowing for more information regarding the influence of several inherent factors on the mass transport limitations, and allow for additional validation of the model beyond simply the quality of the fit.